Market Signals in Value-Based Pricing Premiums and Discounts - Dillon M. Feuz (Journal of Agricultural and Resource Economics, 1999)
There is concern in the beef industry that present marketing practices may be impending the transmission of economic signals from consumers to producers. Presently, fed cattle may be sold on a show list, pen-by-pen, or on an individual head basis, and may be priced using live weight, dressed weight, or grid or formula pricing. Market signals are more likely to reach producers if cattle are priced individually. Current value-based pricing are discussed. Three grid pricing systems are evaluated over six marketing dates using data from 5,520 head of fed cattle. Each of the grids do send the anticipated pricing signals in that marbling and leanness are rewarded. However, the magnitudes of the price signals vary over time and across grids.